Receptor and Molecular Mechanism of AGGF1 Signaling in Endothelial Cell Functions and Angiogenesis. Issue 11 (23rd September 2021) - Wang, Jingjing; Peng, Huixin; Timur, Ayse Anil; Pasupuleti, Vinay; Yao, Yufeng; Zhang, Teng; You, Sun-Ah; Fan, Chun; Yu, Yubing; Jia, Xinzhen; Chen, Jing; Xu, Chengqi; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Angiogenic factor AGGF1 (angiogenic factor with G-patch and FHA [Forkhead-associated] domain 1) promotes angiogenesis as potently as VEGFA (vascular endothelial growth factor A) and regulates endothelial cell (EC) proliferation, migration, specification of multipotent hemangioblasts and venous ECs, hematopoiesis, and vascular development and causes vascular disease Klippel-Trenaunay syndrome when mutated. However, the receptor for AGGF1 and the underlying molecular mechanisms remain to be defined. Approach and Results: Using functional blocking studies with neutralizing antibodies, we identified α5β1 as the receptor for AGGF1 on ECs. AGGF1 interacts with α5β1 and activates FAK (focal adhesion kinase), Src (proto-oncogene tyrosine-protein kinase), and AKT (protein kinase B). Functional analysis of 12 serial N-terminal deletions and 13 C-terminal deletions by every 50 amino acids mapped the angiogenic domain of AGGF1 to a domain between amino acids 604-613 (FQRDDAPAS). The angiogenic domain is required for EC adhesion and migration, capillary tube formation, and AKT activation. The deletion of the angiogenic domain eliminated the effects of AGGF1 on therapeutic angiogenesis and increased blood flow in a mouse model for peripheral artery disease. A 40-mer or 15-mer peptide containing the angiogenic domain blocks AGGF1 function, however, a 15-mer peptide containing a single amino acid mutation from −RDD- to −RGD- (a classical RGD integrin-binding motif) failed to block AGGF1 function. Conclusions: We have identified integrin α5β1 as an EC receptor for AGGF1 and a novel AGGF1-mediated signaling pathway of α5β1-FAK-Src-AKT for angiogenesis. Our results identify an FQRDDAPAS angiogenic domain of AGGF1 crucial for its interaction with α5β1 and signaling.